Responding to Loss : Heideggerian Reflections on Literature, Architecture, and Film - Mugerauer, Robert (Book collections on Project MUSE., 2015)
'The Crossing' by Cormac McCarthy, the Jewish Museum Berlin by Daniel Libeskind, and 'Wings of Desire' by Wim Wenders call on us to face up to, then reflect upon the phenomena of loss, displacement, violence, witnessing, mortality, and responsibility. The way these saturated, overwhelming phenomena come to us requires close and patient focus if we are to adequately receive them in their particularity and depth.